Functionalization of yogurts with Agaricus bisporus extracts encapsulated in spray-dried maltodextrin crosslinked with citric acid - Francisco, Cristhian Rafael Lopes (2018)
Mushroom extracts contain bioactive compounds potentially useful to functionalize foodstuffs. Herein, alcoholic extracts of Agaricus bisporus were studied for their bioactivity and viability as functional ingredients in a food product with high water content (yogurt). Extracts were microencapsulated (to improve their stability and hydrophilicity) by spray-drying, using maltodextrin crosslinked with citric acid as encapsulating material. The effect of thermal treatment (after atomization) on crosslinking and bioactivity of microspheres was tested. The incorporation of free and thermally untreated forms resulted in yogurts with higher initial antioxidant activity (EC 50 values: 214 and 272 mg.mL −1 ) that decreased after 7 days (EC 50 values: 248 and 314 mg.mL −1 ). Contrarily, thermally treated microencapsulated extracts showed higher antioxidant activity after the same period (EC 50 values, 0 days: 106 mg.mL −1 ; 7 days: 48.7 mg.mL −1 ), in result of an effective protection provided by microencapsulation with crosslinked maltodextrin and citric acid. Functionalized yogurts showed an overall maintenance of nutritional properties.